The Relationship Between Anxiety Levels and Cortisol Concentrations in Young and Elderly Primigravida Women - Cahyani, Yunita Indah; Rahman, Abdul; Asni, St. Nur; Lotisna, David; Pelupessy, Nugraha Utama (Journal of Neonatal Surgery, 2025)
Background: Pregnancy is a critical life stage often accompanied by anxiety, particularly in primigravidas of young (<20 years) and advanced maternal age (≥35 years). Anxiety during pregnancy can influence physiological responses, including elevated cortisol levels, which may impact maternal and fetal outcomes. Objective: This study aimed to examine the relationship between anxiety levels and cortisol levels in young and elderly primigravidas. Methods: A cross-sectional analytical study was conducted involving primigravidas aged <20 and ≥35 years. Anxiety was measured using the Perinatal Anxiety Screening Scale (PASS), and cortisol levels were assessed using a validated ELISA method. Results: A significant correlation was observed between PASS scores and cortisol levels (p < 0.05). Elderly primigravidas exhibited higher anxiety and cortisol levels than younger counterparts. Conclusion: There is a significant relationship between anxiety and cortisol levels in both young and elderly primigravidas. Interventions aimed at anxiety reduction may play a role in optimizing maternal hormonal responses and pregnancy outcomes